Kinetics of Thermolysis of a Low-Temperature Tar in the Presence of a Catalyzer Agent with Deposited Metals - Tyanakh, S.; Baikenov, M.I.; Gulmaliev, A.M.; Feng-Yun, Ma; Musina, G.; Khamitova, T.O.; Bolatbay, A.N. (Karagandy University of the name of academician E.A. Buketov, 2022)
The thermal decomposition of low-temperature coal tar (LTCT) obtained from the coals of Shubarkol Komir JSC of the Republic of Qazaqstan in the presence of nanocatalysts with metal oxides (iron, cobalt and nickel) supported on microsilicate was studied for the first time. Microsilicate acts as a carrier and catalyst. Microsilicate is a product of the Karaganda silicon plant of “Tau-Ken.temir” LLP. The main chemical component of the original microsilicate is silicon oxide. The individual and chemical phase composition of the microsilicate was determined using X-ray spectral analysis. The particle size of the initial microsilicate and the mixture of microsilicate with metal oxide catalysts (nickel, cobalt, and iron) was determined using a nanosizer. Stages of thermal decomposition of LTCT and a mixture of LTCT with catalysts under conditions of programmed heating up to 640 °С in a nitrogen atmosphere have been established. On the basis of thermogravimetric analysis, the kinetic parameters (activation energy, mass loss rate, and pre-exponential factor) of LTCT pyrolysis and mixture with added catalysts were determined. The modeless integral isoconversion Ozawa–Flynn–Wall method was used to determine the kinetic parameters. The values of the activation energy for the thermal destruction of the LTCT in the absence and presence of the nanocatalyst ranged from 54.04 to 297.5 kJ/mol. A kinetic compensation effect was revealed, probably due to the multicomponent composition of the LTCT and the influence of added catalysts to the LTCT. The thermogravimetry method showed a high effect of the supported catalysts on the thermal degradation of LTCT. This method was used to determine the values of the activation energy and the pre-exponential degradation factor for the LTCT and the mixture with catalysts at different heating rates, which allows a detailed interpretation of the thermal analysis data. The obtained results of the kinetics of decomposition of LTCT can be used to create a database for mathematical modeling of the process of processing this type of raw material.
Металдармен байытылған катализдік қоспа қатысындағы төментемпературалы шайыр термолизінің кинетикасы
Кинетика термолиза низкотемпературной смолы в присутствии каталитической добавки с нанесенными металлами
Keywords: kinetics; accelerant; microsilica; low-temperature coal tar; thermogravimetric analysis; iron; nickel; cobalt